Adaptation of Sonication-Assisted Matrix Solid Phase Dispersion of Tissues for the Subsequent Extraction of Polycyclic Aromatic Hydrocarbons from Gulf Menhaden (Brevoortia patronus) - Gregory M. Olson; Buffy M. Meyer; Ralph J. Portier (Biochemistry Research International)
A new adaptation based on matrix solid phase dispersion of tissue for the subsequent isolation of polycyclic aromatic hydrocarbons was developed and used for extractions of Gulf menhaden caught during the summer of 2011. Many Matrix Solid Phase Dispersion (MSPD) methods require specific cartridges and other clean-up materials in order to achieve proper extraction. For this study, the tissues were lyophilized prior to applying the adapted MSPD method allowing for a much more complete homogenization with the C18 silica. The tissue was spiked with phenanthrene d10 as a surrogate as a measure of PAH recovery prior to the lyophilisation process to determine if any target compounds were lost and prior to sonication as per the finalized adaptation procedure to determine method efficiency. This technique used C18 silica in a 1 : 1 ratio as the primary homogenizing material for the menhaden tissue matrix and was eluted with dichloromethane (DCM) until visibly clear. The overall study mean recovery was 88%±5% with method detection limits between 0.4 ng/g and 4.4 ng/g tissue dry weight. This adapted protocol has been used exclusively on the analysis of high lipid content fish stocks affected by dispersed and weathered oil from the BP Horizon incident.